Response of Rhizobium-vesicular arbuscular mycorrhizal symbionts on photosynthesis, nitrogen metabolism and sucrose translocation in greengram (Phaseolus radiatus) - THAKUR, A K; PANWAR, J D S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during rainy season of 1994 to study the response of ’PS 16’ and ’Pusa 105’ greengram (phaseolus radiatus L.) to Rhizobium- and vesicular arbuscular mycorrhizal (VAM) fungi. Rhizobium-treated plants bad larger leaf area (9.10%), higher chlorophyll content (11.40%) and photosynthesis activity (21.65%), transpiration (15.89%) and stomatal conductance (19.3 5%) than untreated ones, and thus had higher dry-matter production. Inoculation increased’ the nodulation, nitrate reductase and nitrogenase activity, but the response was significantly higher in the Rhizobium- and VAM-inoculated plants. The translocation pattern (l4C sucrose) was more towards underground portion indual-inoculated plants compared with single inoculation and the uninoculated control.’Pusa 105’ greengram showed higher activity than ’PS 16’ and dual inoculation proved better than single inoculation.